Overview of recent HL-2A experiments. (5th October 2015) - Xu, M.; Duan, X.R.; Dong, J.Q.; Ding, X.T.; Yan, L.W.; Liu, Yi; Song, X.M.; Huang, Y.; Zou, X.L.; Yang, Q.W.; Liu, D.Q.; Rao, J.; et al.
Abstract: Since the last Fusion Energy Conference, the HL-2A experiment has made significant progress in the following areas: (i) physics on low-intermediate-high (L-I-H) transition and pedestal dynamics; (ii) magnetohydrodynamic (MHD) and energetic-particle (EP) physics; (iii) interaction between neoclassical tearing modes (NTMs) and non-local transport; (iv) and edge localized mode (ELM) mitigation by supersonic molecular beam injection (SMBI). Two types of limit-cycle-oscillations (LCOs) were observed in the intermediate phase (I-phase), which indicated a second type of predator-prey process between turbulence and pressure gradient in addition to the conventional predator–prey involving zonal flows and turbulence. It was found that a kink-type MHD mode often crashed prior to the I-H transition, which played a crucial role in triggering H-mode by increasing the edge pressure gradient and E   ×   B flow shear and consequently suppressing turbulent transport. It was also found that impurity concentration played an important role in the multi-transitions between ELM-free H-mode and I-phase. Besides, a quasi-coherent mode around 50–100 kHz was found to be associated with pedestal density gradient saturation in ELM-free H-mode. For the first time, two types of magnetic activities with n   =  0 were observed in the presence of strong tearing modes. Fourier bicoherence analysis suggested that these modes were generated by the nonlinear coupling between Alfvén eigenmodes (AEs) and low-frequency MHD modes. Up- and down-sweeping reverse shear Alfvén eigenmodes (RSAEs) were identified experimentally. The transitions between fishbone and long-lived mode (LLM) were also investigated. The results showed that fishbone could transit from/to LLM and even trigger tearing modes (TMs). For non-local transport, key characteristics of enhanced avalanches in the theory of self-organized criticality (SOC) were identified, including high Hurst exponents and large-scale radial propagation. Experimental results revealed a close correlation between NTMs and non-local transport. In addition, studies on ELM mitigation by SMBI have also progressed substantially.